1989 grain dust explosions stay low - Schoeff, Robert W. (Kansas State University. Dept. of Grain Science and Industry, 2010)
Thirteen grain dust explosions were reported in the U.S. in 1989 according to data compiled by Ralph Regan, FGIS Safety Director, and Robert W. Schoeff, Extension Marketing and Safety Specialist, Kansas State University. This compares to 12 in 1988 and a ten-year average of 20 explosions.
Keywords: Grain dust; Dust explosions